Generalized Kramers’ problem for Lévy particle - Sliusarenko, A.Yu.; Chechkin, A.V. (Вопросы атомной науки и техники, 2007)
We consider a generalization of the classical stochastic problem, namely, how to evaluate the mean escape time and escape probability law of a macroscopic particle, being under the influence of the surrounding medium, from a potential well (Kramers problem). The calculations are executed using the method of numerical integration of an overdamped Langevin equation, in which the random force obeys Lévy stable probability law. The detailed description of the method is given, paying much attention to the correct Langevin equation time-quantization and to creating noise generator for the simulations. The mean escape times and escape probability density functions for the case of a truncated harmonic potential and for the whole admitted region of Lévy indices α are evaluated. Розглянуто узагальнення однієї із типових стохастичних задач – задача про отримання середнього часу вильоту та функції розподілу вильотів макроскопічної частинки із потенціальної ями під дією її оточуючого середовища (задача Крамерса). Ми зупиняємося на випадку обрізаного гармонічного потенціала. Обчислення виконуються методом чисельного інтегрування передемпфованого рівняння Ланжевена, в якому випадкова сила має закон розподілу Леві. Надано детальний опис самого методу, причому особлива увага приділена вірній дискретизації рівняння Ланжевена у часі та побудові генератора шуму для чисельного моделювання. Отримано середні часи вильоту та їх функції розподілу для всієї області значень параметра Леві. Рассмотрено обобщение одной из типовых стохастических задач – задача о получении среднего времени вылета и функции распределения вылетов макроскопической частицы из потенциальной ямы под действием окружающей ее среды (задача Крамерса). Здесь мы останавливаемся на случае обрезанного гармонического потенциала. Вычисления производятся методом численного интегрирования передемпфированного уравнения Ланжевена, в котором случайная сила обладает законом распределения Леви. Дано детальное описание самого метода, причем особое внимание обращено на правильную дискретизацию уравнения Ланжевена во времени и построение генератора шума для численного моделирования. Получены средние времена вылета и их функции распределения для всей области значений параметра Леви.